VDC_100102371237.0X000001. Issue 10 (October 2018) - Anand, Tanya; Ponce, Santa; Pakula, Andrea; Norville, Cindy; Kallish, David; Martin, Maureen; Skinner, Ruby
Ventilator-associated pneumonia (VAP) is linked to increased morbidity and mortality and clinical protocols (VAP bundles) have evolved to minimize VAP. In 2009, a quality improvement project was implemented at our institution to decrease VAP rates in adult trauma patients. AVAP prevention committee was developed, and formal evidence-based education for the nursing and physician staff was introduced. During the study period (2009–2016), 2380 patients required ICU admission to our Level II trauma center. The mean Injury Severity Score was 33 1 12, and there were 17 per cent penetrating and 83 per cent blunt injuries. The early compliance (2010) with the VAP bundle was 65 per cent. Within one year of the implementation of VAP prevention, the compliance increased to >90 per cent. Compliance has been carefully trended and has remained at 100 per cent. All of the aforementioned interventions have resulted in a sustained dramatic decline in VAP, from 12 per cent in 2009 to 0 per cent in 2016. Ongoing education and ICU policy development has become the mainstay of our trauma ICU program. The introduction of evidence-based care education imparted a culture of excellence resulting in favorable outcomes in high-risk trauma patients related to VAP prevention. Ongoing monitoring and education is required to sustain these promising outcomes.